Drug Resistance due to Elaboration of Beta Lactamases and the Role of CTX-M in Enterobacteriaceae - Rida Sohail; Yasmeen Taj; Luqman Satti; Shaista Bakhat (Journal of Bahria University Medical and Dental College, 2022)
The Enterobacteriaceae family are the most common pathogens associated with hospital and community acquired infections worldwide. These bacteria are treated with broad spectrum antibiotics especially 3rd generation cephalosporins. Over the period of time due widespread and rigorous use of these medications, Enterobacteriaceae has developed antibiotic resistance (AMR). Among all, the most compelling antibiotic resistance mechanism is production of -lactamases enzymes by this microorganism. Over the course of time -lactamase has evolved more than 1300 distinct enzymes. Amongst these most deleterious is extended spectrum beta lactamases (ESBL). ESBL producing Enterbacteriacaeae are responsible for a high number of deaths worldwide. These enzymes are considered challenging as they are difficult to be identified in the laboratory wShich cause delay in diagnosis and administration of appropriate antimicrobial therapy. The coexistence of ESBL with other antibiotic resistance gene is another therapeutic challenge rendering empirical antibiotic treatment ineffective.